Metodología para optimización de intersecciones viales a nivel con congestión vehicular en ciudades de hasta 300000 habitantes - Quezada Jaya, Rómulo Giovanni (Machala; Universidad Técnica de Machala, 2024)
The limited theoretical information on methodologies for optimising at-grade road intersections and the vehicular congestion that occurs at these intersections has been one of the limitations for the development of this research. Despite this, it was possible to accurately describe the aspects of the local reality, the social and scientific relevance, and this research is valid, up-to-date and has a significant impact on the knowledge of the reality of urban roads and their intersections. This work was carried out following the lines of research of the Master's Programme in Civil Engineering, mention in roads, and responds to the demands of the local cantonal governments, being the Autonomous Decentralised Municipal Government of Machala Canton, which provided the relevant information for analysis, the Centre for Postgraduate Studies of the Technical University of Machala contributed with advisors, technical support and technological equipment. This research aims to provide a solution to the problem: How the optimisation of at-grade road intersections will reduce traffic congestion in cities of up to 300,000 inhabitants, by studying the optimisation of at-grade road intersections and their traffic congestion, which will be based on the theories and concepts of the national and international Geometric Design Standards for Roads. As a purpose, the thesis presents a comprehensive methodology based on state-of-the-art technology to characterise intersections and simulate alternatives to reduce traffic congestion. The proposed methodology would allow the optimisation of congested intersections in cities of up to 300,000 inhabitants. The case study is the Redondel El Bananero intersection in the city of Machala, Ecuador. The methodology involves characterising traffic by measuring vehicle flow, speed and vehicle classification with automatic equipment. Then alternatives are analysed in simulation software and finally the optimisation is implemented. It is based on the use of pneumatic counters to obtain reliable traffic data. The methodological scheme includes measurements, analysis, modelling, simulation and proposal of improvements. The simulation in Aimsun evaluated 5 scenarios: current situation, with traffic lights, with turn lanes, increased capacity and combination of turn lanes with increased capacity. The best results were obtained with the combined measure. The conclusions indicate that turn lanes on access to the roundabout plus increased road capacity reduce congestion and improve the level of service. It is recommended that these measures be implemented gradually, evaluating their effectiveness
La limitada información teórica sobre metodologías para optimización de intersecciones viales a nivel y la congestión vehicular que se producen en estas, ha sido uno de los limitantes para el desarrollo de esta investigación, pese a esto se pudo describir en forma precisa los aspectos de la realidad local, la relevancia social y científica, además esta investigación, tiene vigencia, actualidad y significativo impacto en el conocimiento de la realidad de las vías urbanas y sus intersecciones. Este trabajo se ejecutó siguiendo las líneas de investigación del Programa de Maestría de Ingeniería Civil, mención vialidad, y responde a las demandas de los gobiernos locales cantonales, siendo el Gobierno Autónomo Descentralizado Municipal del Cantón Machala, que facilito la información pertinente para su análisis, el Centro de Estudios de Posgrados de la Universidad Técnica de Machala aporto con asesores, técnicos de apoyo y equipos tecnológicos. Esta investigación pretende dar solución al problema: ¿Como la optimización de intersecciones viales a nivel disminuirán la congestión vehicular en ciudades de hasta 300000 habitantes?, para ello se estudió la optimización de intersecciones viales a nivel y su congestión vehicular, las mismas que se sustentaran en las teorías y conceptos de las Normas de Diseño Geométrico de Carreteras, nacionales e internacionales. Como propósito, la tesis presenta una metodología integral basada en tecnología de punta para caracterizar intersecciones y simular alternativas que permitan reducir la congestión vehicular. La propuesta metodológica permitiría la optimización de intersecciones viales con congestión vehicular en ciudades de hasta 300.000 habitantes. El caso de estudio es la intersección del Redondel El Bananero en la ciudad de Machala, Ecuador. La metodología implica caracterizar el tráfico mediante mediciones de flujo vehicular, velocidad y clasificación de vehículos con equipos automáticos. Luego se analizan alternativas en software de simulación y finalmente se implementa la optimización. Se fundamenta en el uso de contadores neumáticos para obtener datos confiables del tráfico. El esquema metodológico incluye mediciones, análisis, modelación, simulación y propuesta de mejoras. La simulación en Aimsun evaluó 5 escenarios: situación actual, con semáforos, con carriles de giro, aumento de capacidad y combinación de carriles de giro con aumento de capacidad. Los mejores resultados se obtuvieron con la medida combinada. Las conclusiones indican que los carriles de giro en accesos al redondel más aumento de capacidad vial reducen la congestión y mejoran el nivel de servicio. Se recomienda implementar estas medidas de forma gradual, evaluando su efectividad
Keywords: INTERSECCION VIAL; CONGESTION VEHICULAR; FLUJO VEHICULAR; DEMANDA VIAL